Observation of an alternative χc0(2P) candidate in e+e−→J/ψDD¯ - Bhardwaj, V. (Council of Scientific Research Integration, 2017)
Synthesis and X-ray structural characterization of pyridine-2- carboxaldehyde thiosemicarbazone (L), and its metal complexes, [Cu(L)(OH2)](ClO4)2 and [Pb(L)(ONO2)2]n are reported. X-ray diffraction reveals that the metal centres in the two complexes are distorted square planar and square pyramid geometries, respectively. Among the three compounds [Cu(L)(OH2)](ClO4)2 is found to be active against human keratinocyte cell line.
Only IISERM authors are available in the record.
Keywords: Anticancer activity; Coordination chemistry; Copper